Digitalisasi Pencatatan Keuangan UMKM melalui Pelatihan Penggunaan Aplikasi Buku Warung di Desa Tunggulsari Kabupaten Kendal - Eka Yuliyanti; Andi Kartika; Anis Turmudhi; Rahmania Mustahidda; Zati Rizka Fadhila (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service program is conducted in Tunggulsari Village, Brangsong District, Kendal Regency, with a focus on empowering Micro, Small, and Medium Enterprises (MSMEs) through training in digital financial record-keeping using the Buku Warung application. Tunggulsari Village has strong local economic potential in the snack food industry, including gadung chips, opak, and breadfruit. The program is implemented through stages of business identification, MSME mapping, socialization, and direct assistance in applying the financial record-keeping application. The results of this activity indicate that MSME actors have gained a better understanding of the importance of financial record-keeping and are beginning to adopt digital technology in managing their businesses. Challenges faced include limited time for socialization and uneven participation among MSME actors. Nevertheless, this activity has successfully improved the financial literacy and managerial skills of business actors and has encouraged digital transformation in the rural MSME environment. This program also strengthens the role of higher education institutions in supporting community-based economic development through an applicable and sustainable technological approach.